Empowerment, Deliberative Development and Local Level Politics in Indonesia : Participatory Projects as a Source of Countervailing Power /: Participatory Projects as a Source of Countervailing Power. (October 2007) - Gibson, Christopher L (Christopher Laurence); Woolcock, Michael J. V, 1964-
No abstract available